Does the VDR gene polymorphism influence the efficacy of denosumab therapy in postmenopausal osteoporosis? - Wawrzyniak, Anna; Skrzypczak-Zielińska, Marzena; Michalak, Michał; Kaczmarek-Ryś, Marta; Ratajczak, Alicja Ewa; Rychter, Anna Maria; Skoracka, Kinga; Marcinkowska, Michalina; Słomski, Ryszard; Dobrowolska, Agnieszka; Krela-Kaźmierczak, Iwona (Frontiers in Endocrinology, 2023)
Introduction: One of the challenges of personalized medicine is a departure from traditional pharmacology toward individualized, genotype-based therapies. Postmenopausal osteoporosis is a prevalent condition requiring intensive treatment, whose effects are measurable only after a long time, and the goal is bone fracture prevention. This study aimed to determine the influence of VDR gene variation on anti-osteoporotic one-year treatment with denosumab in 63 Polish women with postmenopausal osteoporosis. Materials and Methods: The correlation between bone mineral density (BMD) of the lumbar vertebral column (L1–L4) and femoral neck, and genotype distributions for the ApaI, BsmI, FokI, and TaqI variants of the VDR gene was analyzed. Bone fractures during denosumab therapy were also investigated. Results: In the case of the Bsml polymorphism, female patients with BB and Bb genotypes had statistically significantly higher values of BMD and T-score/Z-score indicators, which persisted after a year of denosumab treatment. Our results indicated that the Bsml polymorphism contributes to better bone status, and, consequently, to more efficient biological therapy. The study did not reveal significant differences between changes (delta) in BMD and genotypes for the analyzed VDR gene loci. In the entire study group, one bone fracture was observed in one patient throughout the yearlong period of denosumab therapy. Conclusions: BB and Bb genotypes of the Bsml polymorphism of the VDR gene determine higher DXA parameter values both before and after one-year denosumab therapy in postmenopausal women with osteoporosis.